PERAN STRES KERJA MEMEDIASI BEBAN KERJA TERHADAP KEPUASAN KERJA KARYAWAN KANTOR CABANG PT.BINTANG SIDORAYA - Yulistana, Dhita; Satrya, I Gusti Bagus Honor (E-Jurnal Manajemen; Vol 11 No 1 (2022)DO - 10.24843/EJMUNUD.2022.v11.i01.p04, 2022)
A company must pay attention to how its employee can enjoy his/her job, or get what they expect. This research was conducted at PT. Bintang Sidoraya, a company engaged in the beverage distribution business, it has been established since 1981. This study aims to determine the relationship between the workload and work stress with job satisfaction, and to determine the role of work stress in mediating the relationship between the workload and job satisfaction. The population in this study were the employees of PT. Bintang Sidoraya has a total of 47 employees. The analysis technique in this study uses path analysis. The results of the analysis show that workload has a positive and significant effect on work stress. Workload also has a negative and significant effect on job satisfaction. Work stress has a negative and significant effect on job satisfaction. The results of this study also indicate that Work stress is believed to partially mediate the relationship between workload and job satisfaction. The company is expected to be able to provide workloads in accordance with the abilities and capabilities of the employees, the company is expected to provide recreational time between the employees so that the relationship between themis more intimate and maintainsits positivity, and the company is expected to be able to provide more rewards for employees both in terms of support in the form of gratitude for the work that has been completed properly and provide a salary that is in accordance with the workload felt by the employee. Keywords: Workload, Work stress, Job satisfaction